2022
DOI: 10.17219/acem/149566
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic signature based on the expression profile of the ferroptosis-related long non-coding RNAs in hepatocellular carcinoma

Abstract: Background.Ferroptosis is a special form of cell death with extensive biological associations with various cancers; however, the role of aberrantly expressed ferroptosis-related long non-coding RNAs (lncRNAs) in hepatocellular carcinoma (HCC) remains unclear.Objectives. To explore the role and prognostic value of ferroptosis-related lncRNAs in HCC and to screen potential therapeutic targets. Materials and methods.The RNA-seq data for 424 HCC patients and clinical data for 377 HCC patients were obtained from Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The AC009549.1, AL136419.3 has been reported to associated with progression and prognosis in colorectal cancer, head and neck squamous cell carcinoma, [29,30] . The AL928654.1, MKLN1-AS, TMCC1-AS1 were found as lncRNAs related to the progression of HCC [31][32][33] , while AC138696.2, AL449106.1 have not been studied yet. Subsequently, HCC patients were separated into high-and low-risk groups based on the intermediate risk score, and the high-risk group had apparently poor clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…The AC009549.1, AL136419.3 has been reported to associated with progression and prognosis in colorectal cancer, head and neck squamous cell carcinoma, [29,30] . The AL928654.1, MKLN1-AS, TMCC1-AS1 were found as lncRNAs related to the progression of HCC [31][32][33] , while AC138696.2, AL449106.1 have not been studied yet. Subsequently, HCC patients were separated into high-and low-risk groups based on the intermediate risk score, and the high-risk group had apparently poor clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…All these lincRNAs played essential roles in HCC biological process. Studies showed that lncRNA AC012073.1 played an oncogenic role in influencing HCC prognosis and was associated with N6-methyladenosine and ferroptosis (40,41). AL031985.3 was associated with pyroptosis, immune response, ferroptosis, glycolysis, and autophagy in HCC (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many studies are focused on precision genomic medicine, and many predictive models have been developed in an attempt to predict patient outcomes. Many lncRNAs, like N6methyladenosine-related lncRNAs, ferroptosis-related lncRNAs, pyroptosis-related lncRNAs, glycolysis-Related lncRNAs, contributed to a better understanding of HCC biological processes and helped predict the prognosis of HCC (40)(41)(42)(43)(44)(45). However, few studies concentrated on CD4+ Tconv-related lncRNAs, and the roles of CD4+ Tconv-related lncRNAs remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a unique pattern of cell death that has received extensive interest, especially in the area of tumorigenesis and therapies [29]. Several research studies have mainly concentrated on developing DEFRlncRNA signatures to assess the prognosis of tumor patients [16,18,[30][31][32]. Nevertheless, the vast majority of signatures are established on the basis of the expression levels of quantitative transcripts.…”
Section: Discussionmentioning
confidence: 99%